2020
DOI: 10.3390/jcm9041139
|View full text |Cite
|
Sign up to set email alerts
|

RNAs and Gene Expression Predicting Postoperative Atrial Fibrillation in Cardiac Surgery Patients Undergoing Coronary Artery Bypass Grafting

Abstract: Postoperative atrial fibrillation (POAF) is linked with increased morbidity, mortality rate and financial liability. About 20–50% of patients experience POAF after coronary artery bypass graft (CABG) surgery. Numerous review articles and meta-analyses have investigated links between patient clinical risk factors, demographic conditions, and pre-, peri- and post-operative biomarkers to forecast POAF incidence in CABG patients. This narrative review, for the first time, summarize the role of micro-RNAs, circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…A study by Efird et al [37] of 13,594 patients undergoing first-time, isolated CABG found that POAF is significantly associated with white race (95% CI, p < 0.0001). Furthermore, there has been substantial evidence to suggest that there is a large genetic component to a person's risk of POAF, opening the potential for biomarkers to be used to predict POAF [38]. However, while the evidence is promising, the cohort sizes used for these studies are too small to be representative of a true population size thus more Analysis of Circulating miR-1, miR-23a, and miR-26a in Atrial Fibrillation Patients Undergoing Coronary Bypass Artery Grafting Surgery [13] There were reduced expression levels for miRNA-23a (p = 0.02) and -26a (p = 0.01) in the POAF group during the postoperative period in comparison to preoperative results with receiver operating curve of 0.63 (confidence interval [CI]: 0.51-0.74) and 0.66 (95% CI: 0.55-0.77), respectively [13] miRNA-199a…”
Section: Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Efird et al [37] of 13,594 patients undergoing first-time, isolated CABG found that POAF is significantly associated with white race (95% CI, p < 0.0001). Furthermore, there has been substantial evidence to suggest that there is a large genetic component to a person's risk of POAF, opening the potential for biomarkers to be used to predict POAF [38]. However, while the evidence is promising, the cohort sizes used for these studies are too small to be representative of a true population size thus more Analysis of Circulating miR-1, miR-23a, and miR-26a in Atrial Fibrillation Patients Undergoing Coronary Bypass Artery Grafting Surgery [13] There were reduced expression levels for miRNA-23a (p = 0.02) and -26a (p = 0.01) in the POAF group during the postoperative period in comparison to preoperative results with receiver operating curve of 0.63 (confidence interval [CI]: 0.51-0.74) and 0.66 (95% CI: 0.55-0.77), respectively [13] miRNA-199a…”
Section: Ethnicitymentioning
confidence: 99%
“…Polymorphism rs2200733 at chromosome 4q25 is associated with atrial fibrillation recurrence after radiofrequency catheter ablation in the Chinese Han population [41] Allelic analysis was conducted and a strong association was found between rs2200733 and AF recurrence after ablation (p = 0.011) [41] trials must be carried out with larger cohorts before a definitive conclusion is drawn (Table 1, Ref. [12,13,19,[38][39][40][41]) [38].…”
Section: Ethnicitymentioning
confidence: 99%
“…In a recent study on the four left atrial appendages of patients with nonvalvular persistent atrial fibrillation (NPAF) and four normal controls, a total of 296 significantly dysregulated circRNA transcripts were obtained via RNA sequencing, 238 upregulated and 58 downregulated; hsa_circ_002085 and hsa_circ_001321 showed potential as NPAF biomarkers [ 63 ]. Furthermore, Khan et al screened the plasma circRNA expression profiles of 769 patients with and without postoperative atrial fibrillation (PoAF), and found that the expression of hsa_circRNA_025016 was upregulated in patients with newly onset AF after isolated off-pump coronary-artery bypass grafting, and positively correlated to fasting blood glucose [ 64 ]. Results demonstrated that plasma hsa_circ_025016 holds potential as a biomarker for the prediction of PoAF.…”
Section: Circrna Serves As Biomarkers In Scd-related Diseasesmentioning
confidence: 99%
“…For instance, an increase in circulating levels of miR-320a has been noted to be correlated with development of adverse remodeling, such as wall thinning and dilation of the LV after PCI, which can promote the progression to heart failure ( Galeano-Otero et al, 2020 ). Khan et al (2020) have carried out a thorough analytical review of research to date surrounding the levels of miRNAs in blood or tissue extracted during CABP to predict the development of atrial fibrillation after CABG. Whilst many small studies have found increased levels of certain miRNAs correlated to arrhythmia development, the authors recognize that these have not been validated elsewhere in the literature, and many do not take into account changes in miRNA levels that may occur upon reperfusion.…”
Section: Role Of Long Non-coding Rnas and Micro Rnas In Heart Diseasementioning
confidence: 99%